Analysis of the Translation of the Song “Water Under the Bridge” by Adeke’s Version - Safitri, Diya; Syahrial, Syahrial; Maisarah, Ira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the translation strategy applied to translate the lyrics of the song